Repatriating Polanyi: Market Society in the Visegrad States - Hann, Chris (Central European University Press, 2019)
Karl Polanyi’s “substantivist” critique of market society has renewed topicality in the era of neoliberal globalization. Polanyi (1886–1964) is popular among critical theorists and radical political economists, but also with ecological activists, anti-globalization campaigners and all who sense that ongoing financial turmoil is symptomatic of a deeper crisis threatening the compatibility of capitalism and democracy. The author reclaims the polymath Karl Polanyi for contemporary anthropology, especially economic anthropology. The book furthermore takes his ideas back to Central Europe, where he grew up. The Polanyian approach is applied to the communist economy, with particular reference to the “market socialist” economy which evolved under János Kádár in Hungary. The same lens is used to investigate the consequences of the demise of communist power since 1990, primarily on the basis of ethnographic investigations in Hungary and South-East Poland. Stretching the discussion on Polanyi’s great transformation – for which there is considerable international interest – in the context of neoliberalization onto the concept of Eurasia, and then bringing this into conversation with the rise of neo-nationalism in Hungary and Poland and beyond as the form that the great transformation is currently taking in the region, relates Hann’s work powerfully to the current political turbulence.
Anthropology; Political Science
Keywords: Hungary; Poland; communist economy; economic history; market socialist economy; neo-nationalism; political economy

Capitalism in Transformation: Movements and Countermovements in the 21st Century - Atzmüller, Roland; Aulenbacher, Brigitte; Brand, Ulrich; Décieux, Fabienne; Fischer, Karin; Sauer, Birgit (Edward Elgar Publishing, 2019)
Presenting a profound and far-reaching analysis of economic, ecological, social, cultural and political developments of contemporary capitalism, this book draws on the work of Karl Polanyi, and re-reads it for our times. The renowned authors offer key insights to current changes in the relations between the economy, politics and society, and their ecological and social effects.
Sociology
Keywords: biography; capitalism; countermovement; fictitious commodities